Enhancing the effects of nusinersen with cybernic treatment using Hybrid Assistive Limb (HAL) in spinal muscular atrophy: a real-world case series and exploratory cohort analysis - Takashi Nakajima; Toshio Saito; Akihiro Hashiguchi; Taiki Nakabayashi; Kazuki Kodera; Kota Utsumi; Takeshi Kanayama; Haruka Urabe; Satoru Kinoshita (Orphanet Journal of Rare Diseases)
Abstract Background Nusinersen therapy for spinal muscular atrophy (SMA) provides significant functional improvement when initiated pre-symptomatically or early in life. However, challenges remain in diverse populations with longer disease duration. In Japan, innovative cybernic therapy with the Hybrid Assistive Limb (HAL) is gaining traction in treating neuromuscular diseases. This observational study investigated whether combining HAL therapy with nusinersen and conventional physiotherapy yields functional improvements in SMA, irrespective of disease duration or age. Functional improvement indicators included the Hammersmith Functional Motor Scale-Expanded (HFMSE) and Revised Upper Limb Module (RULM) scores, and the 2-minute walk test (2MWT), measured 15 months post-nusinersen initiation. A cohort analysis of a selected case series was conducted. Results Twelve patients with SMA type 2 or 3 who met the criteria of being able to walk with a hoist and began nusinersen treatment > 40 months post-disease onset were selected for longitudinal clinical assessment. Cohort 1 (n = 5, mean age 36.0 years) underwent HAL therapy, while Cohort 2 (n = 7, 24.6 years) did not. Baseline characteristics, except mean age, were similar across cohorts. In Cohort 1, the period from baseline (nusinersen initiation) to HAL therapy ranged from 0 to 8.8 months. HFMSE scores improved in both cohorts at 15 months; the least squares mean (LSM) change from baseline (95% confidence interval [CI]) was 4.7 points (2.2, 7.3) in Cohort 1 and 2.9 points (0.7, 5.1) in Cohort 2. Clinically meaningful improvement of 3.0 points in HFSME was exceeded by four of five patients in Cohort 1 and three of seven in Cohort 2. The LSM change from baseline in RULM was 2.2 points (95% CI 1.0, 3.3) in Cohort 1, exceeding the minimal clinically important difference of 0.5–1.0 points, but remained unchanged in Cohort 2 due to ceiling effects (− 0.2; −1.5, 1.2; p = 0.016). The LSM change from baseline in the 2MWT had improved in Cohort 1 (34.57 m; 95% CI 4.57, 64.57), but not in Cohort 2 (− 3.86; −37.75, 30.03). Conclusions In patients with SMA type 2 and 3, clinically meaningful improvements in multiple indicators were observed when HAL was combined with nusinersen, even when treatment commenced many years after disease onset. Registration jRCT1090220400 ( https://jrct.niph.go.jp/en-latest-detail/jRCT1090220400 ).